Peer interaction, writing proficiency, and the quality of collaborative digital multimodal composing task: Comparing guided and unguided planning. (June 2022) - Kim, YouJin; Kang, Sanghee; Nam, Yunjung; Skalicky, Stephen
Abstract: In the current digital era, writing is viewed as communication beyond monomodal written language, and thus the importance of multimodal literacies has received increased attention from language researchers. Recently, language educators have begun incorporating the use of collaborative digital multimodal composing (DMC) tasks in the language learning classroom. However, because DMC tasks are rather new, different approaches to implementing DMC tasks have not been explored. In the current study, we investigated the implementation of DMC tasks in a Korean high school English classroom. Through a combined perspective rooted in multimodal literacies and task-based language teaching (TBLT), we examined the role of guided and unguided pretask planning on the amount of peer interaction (operationalized as DMC episodes) during pretask planning and DMC task performance. We also examined the extent to which writing proficiency, pretask planning condition, and the number of DMC episodes predicted performance scores of collaborative DMC task outcomes. To do so, we analyzed data from DMC tasks and English writing tests completed by 116 Korean high school students over a period of eight days. Students' interactions during planning time and task performance were recorded and transcribed to identify different DMC episodes. Both the written essays and DMC tasks were scored using analytic rubrics. The results showed that a larger number of DMC episodes were produced by the guided planning group when compared to the unguided planning group during planning time, whereas the opposite picture was found during task performance. This increased number of episodes during guided planning also predicted higher DMC task scores when compared to the unguided group. Additionally, there was some evidence of a small association between English writing proficiency and the quality of DMC task outcomes.